ANALISIS BIMBINGAN BAGI ANAK BERKELAINAN KHUSUS SEKOLAH DASAR GMIT 022 MOLLA - Fenti Kuang; Dermolinda Maipan, Esriyanti Lakapada, Yessy Mata, Petrus Mau Tellu Dony, Yermia S. Wabang (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The purpose of this study was to examine guidance services for children with special needs at GMIT 022 Mola Elementary School, Mola Village, Alor Regency. The research employed a descriptive qualitative approach, using interviews, observations, and documentation involving the fifth-grade homeroom teacher, special education assistant teachers, and students at GMIT 022 Mola Elementary School. The results of this study indicate that teachers have provided individualized and situational guidance services, with an emphasis on empathetic approaches and emotional support. Students have benefited from these services, and the teachers play essential roles as facilitators, motivators, and counselors. Challenges include a shortage of professionals, limited facilities, and insufficient teacher understanding of special needs. The study recommends regular teacher training, improved facilities, and strengthened collaboration between schools, parents, and the education department.